Secondary Angio-Embolization After Emergent Pelvic Stabilization and Pelvic Packing Is a Safe Option for Patients With Persistent Hemorrhage From Unstable Pelvic Ring Injuries - Lustenberger, Thomas; Störmann, Philipp; Eichler, Kathrin; Nau, Christoph; Janko, Maren; Marzi, Ingo (Frontiers in Surgery, 2020)
Introduction: In patients with severe pelvic ring injuries, exsanguinating hemorrhage represents the major cause of death within the first 24 hours. Mechanical pelvic stabilization and surgical hemostasis by pelvic packing aim to control venous bleeding. Angiography and embolization have emerged as methods for addressing arterial bleeding. The aim of this study was to assess the incidence of postoperative angio-embolization following mechanical pelvic ring injury stabilization and pelvic packing. The sources of ongoing bleeding and patient’s outcome were evaluated. Patients and Methods: Retrospective observational cohort study at a single academic level I trauma center, reviewing all patients with pelvic ring injuries admitted from 01/2010 to 12/2019. Patients with emergent mechanical pelvic ring stabilization (supraacetabular external fixator and/or pelvic C-clamp) and direct pre-peritoneal pelvic packing were further analyzed. Patients that underwent postoperative angio-embolization were compared with those that did not. All postoperative angio-embolizations were evaluated with regards to bleeding sources and type of embolization. Results: During the study period, 39 patients required immediate mechanical pelvic stabilization and direct pre-peritoneal pelvic packing. Of these, 12 patients (30.8%) underwent a postoperative angio-embolization. Bleeding sources identified were the superior gluteal artery in 6 cases, the obturator artery in 2 cases, the internal pudendal artery in 2 cases and unnamed branches of the internal iliac artery in 3 cases. In 11 patients, a selective embolization of the bleeding artery was performed; in 1 patient, an unilateral complete occlusion of the internal iliac artery was necessary to control the bleeding. Mean time from admission to surgery was 52.8 ± 14.7 minutes and the mean time from admission to angio-embolization was 189.1 ± 55.5 minutes. Three patients died in the further hospital course due to multiple organ failure (n=2) and traumatic brain injury (n=1). Conclusion: Secondary angio-embolization after external pelvic fixation and pre-peritoneal pelvic packing was effective in controlling ongoing bleeding. In all patients, angio-embolization was safely performed on the way from the operating room to the intensive care unit. The most frequent bleeding source was the superior gluteal artery, which is difficult to surgically address, further highlighting the importance of angio-embolization in the management algorithm.